Differential effect of sympathetic activation on tissue oxygenation in gastrocnemius and soleus muscles during exercise in humans. Issue 2 (6th December 2013) - Horiuchi, Masahiro; Fadel, Paul J.; Ogoh, Shigehiko
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? The normal ability of sympathetic nerves to cause vasoconstriction is blunted in exercising skeletal muscle, a phenomenon termed 'functional sympatholysis'. Animal studies suggest that functional sympatholysis appears to occur preferentially in fast‐twitch type II glycolytic compared with slow‐twitch type I oxidative skeletal muscle. We asked whether these findings can be extended to humans. What is the main finding and its importance? We show that skeletal muscles composed largely of fast‐twitch type II fibres may also be more sensitive to functional sympatholysis in humans, particularly at lower exercise intensities. Additionally, independent of muscle fibre type composition, the magnitude of sympatholysis is strongly related to exercise‐induced increases in metabolic demand. Animal studies suggest that functional sympatholysis appears to occur preferentially in glycolytic (largely type II) compared with oxidative (largely type I) skeletal muscle. Whether these findings can be extended to humans currently remains unclear. In 12 healthy male subjects, vasoconstrictor responses in gastrocnemius (i.e. primarily type II) and soleus muscles (i.e. primarily type I) were measured using near‐infrared spectroscopy to detect decreases in muscle oxygenation (HbO2) in response to sympathetic activation evoked by a cold pressor test (CPT). The HbO2 responses to a CPT at rest were compared with responses during steady‐state plantar flexion exercise (30 repetitions min−1) performed at 10, 20 and 40% maximal voluntary contraction (MVC) for 6 min. In resting conditions, HbO2 at the gastrocnemius (−14 ± 1%) and soleus muscles (−16 ± 1%) decreased significantly during CPT, with no differences between muscles. During planter flexion at 20% MVC, the change in HbO2 in response to the CPT was blunted in gastrocnemius but not soleus, whereas during 40% MVC both muscles exhibited a significant attenuation to sympathetic activation. The decreases in HbO2 in response to the CPT during exercise were significantly correlated with the metabolic demands of exercise (the decreases in HbO2 in response to steady‐state plantar flexion) in both gastrocnemius and soleus muscles. Collectively, these results suggest that skeletal muscles composed mainly of glycolytic type II fibres are more sensitive to functional sympatholysis, particularly at lower intensities of exercise. Moreover, the blunting of sympathetic vasoconstriction during exercise is strongly related to metabolic demand; an effect that appears independent of fibre type composition.